Assessment the efficiency of certain different insecticides against both spiny and pink bollworms on cotton crop - Sharaf, Fayza H. (2003)
Three sprays of certain different insecticides were carried out to evaluate their efficiency against both pink bollworm Pectinophora gossypiella (Saund.) and the spiny bollworM Earias insulana (Boisd.) infesting cotton plants under field conditions during 2000 and 2001 seasons. Tested insecticides were received from three chemical groups. 4 pyrethroids, 2 organophosphates and one carbamate. The two organophosphates insecticides had the same active ingredient but differ in their formulations. Tested pyrethroids were the most effective which induce the highest %reduction in bollworms larvae population during two seasons, followed by carbamates then organophosphorus insecticides except Dursban (OP) was active than carbamate during 2000 season. Results indicated that, overall mean percent of reduction in population density of bollworms during 2001 was more compared to that of 2000 season for all treatments.
Includes reference.
Summary in Arabic.
1
Keywords: Cotton -- Diseases and pests -- Control; Insecticides; Pink bollworm -- Control; Earias insulana